2016
DOI: 10.1021/acsami.6b07252
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Artificial Antibodies: Plasmonic Biosensors with Improved Selectivity

Abstract: Molecular imprinting, which involves the formation of artificial recognition elements or cavities with complementary shape and chemical functionality to the target species, is a powerful method to overcome a number of limitations associated with natural antibodies. An important but often overlooked consideration in the design of artificial biorecognition elements based on molecular imprinting is the nonspecific binding of interfering species to noncavity regions of the imprinted polymer. Here, we demonstrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 49 publications
(86 reference statements)
0
36
0
Order By: Relevance
“…We have previously demonstrated the feasibility of molecular imprinting on gold nanostructures, which serve as nanotransducers for plasmonic biosensors . In the case of artificial antibodies, the molecular imprinting process on gold nanorods (AuNRs) involves multiple steps as schematically illustrated in Figure A.…”
mentioning
confidence: 99%
“…We have previously demonstrated the feasibility of molecular imprinting on gold nanostructures, which serve as nanotransducers for plasmonic biosensors . In the case of artificial antibodies, the molecular imprinting process on gold nanorods (AuNRs) involves multiple steps as schematically illustrated in Figure A.…”
mentioning
confidence: 99%
“…6,7 We recently demonstrated plasmonic biosensors based on artificial antibodies achieved through molecular imprinting on the nanotransducer surface. 810 Artificial antibodies to a kidney injury biomarker had no change in analyte recognition over a pH range of 4.5–8.5 and specific gravity up to 1.03. 9 Apart from significantly improving the stability and lowering the cost of the biosensors, use of artificial antibodies instead of the natural antibodies as biorecognition elements significantly shortens the bioassay development time as the synthetic imprinting approach can be rapidly applied to a broad class of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, experiments have shown that although the MCS functional monomer indeed increases the adsorption capacity of MIPs, it does not improve the specific adsorption capacity. Sulfobetaine methacrylate (SBMA) can increase the specific adsorption , and NIPAM can endow the imprinted material with temperature sensitivity. Therefore, a protein imprinted material with both responsiveness and specificity has been prepared from an environmentally responsive macromolecular chain structure and an anti‐protein adsorption structure, which attaches to the surface of the imprinted polymer.…”
Section: Introductionmentioning
confidence: 99%